Gingivitis and Oral Health Diseases Related to Pregnancy - Talebessy, Rio; Steffi Cecilia (Phlox Institute: Indonesian Medical Research Organization, 2023)
Pregnancy gingivitis is a common condition characterized by gum inflammation, swelling, and bleeding. Hormonal fluctuations during pregnancy can increase susceptibility to dental infections, particularly in teeth and gums. Factors such as hormonal fluctuations, morning sickness, dietary changes, heightened gum sensitivity, and decreased dental care practices can contribute to this issue. Although hormonal changes do not directly cause dental infections, they can heighten the susceptibility to gum issues and potentially exacerbate the progression of dental infections. This review provides a comprehensive description of pregnancy gingivitis and its contributing factors. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding gingivitis and hormonal changes in pregnancy. The search was performed using the terms: (1)